Reduction in the Prevalence of Healthcare-Associated Infections in U.S. Acute Care Hospitals, 2015 vs 2011. (4th October 2017) - Magill, Shelley S; Wilson, Lucy E; Thompson, Deborah L; Ray, Susan M; Nadle, Joelle; Lynfield, Ruth; Janelle, Sarah J; Kainer, Marion A; Greissman, Samantha; Dumyati, Ghinwa; Beldavs, Zintars G; Edwards, Jonathan R; et al.
Abstract: Background: A 2011 prevalence survey conducted by CDC and the Emerging Infections Program (EIP) showed that 1 in 25 hospital patients had ≥1 healthcare-associated infection (HAI). We repeated the survey in 2015 to assess changes in HAI prevalence.​ Methods: In EIP sites (CA, CO, CT, GA, MD, MN, NM, NY, OR, TN) hospitals that participated in the 2011 survey were recruited for the 2015 survey. Hospitals selected 1 day from May–September 2015 on which a random patient sample was identified from the morning census. Trained EIP staff reviewed patient medical records using comparable methods and the same National Healthcare Safety Network HAI definitions used in 2011. Proportions of patients with HAIs were compared using chi-square tests; patient characteristics were compared using chi-square or median tests (OpenEpi 3.01, SAS 9.3). Results: Data were available from 143 hospitals that participated in both surveys; data from 8954 patients in the 2011 survey were compared with preliminary data from 8833 patients in the 2015 survey. Patient characteristics such as median age, days from admission to survey, and critical care location were similar. Urinary catheter prevalence was lower in 2015 (1, 589/8, 833, 18.0%) compared with 2011 (2, 052/8, 954, 22.9%, P  < 0.0001), as was central line prevalence (2015: 1, 539/8, 833, 17.4%, vs. 2011: 1, 687/8, 954, 18.8%, P  = 0.02). The proportion of patients with HAIs was lower in 2015 (284/8, 833, 3.2%, 95% confidence interval [CI] 2.9–3.6%) than in 2011 (362/8, 954, 4.0%, 95% CI 3.7–4.5%, P  = 0.003). Of 309 HAIs in 2015, pneumonia (PNEU) and Clostridium difficile infections (CDI) were most common (Figure); proportions of patients with PNEU and/or CDI were similar in 2015 (130/8833, 1.5%) and 2011 (133/8954, 1.5%, P  = 0.94). A lower proportion of patients had surgical site (SSI) and/or urinary tract infections (UTI) in 2015 (77/8833, 0.9%) vs. 2011 (136/8954, 1.5%, P  < 0.001). Conclusion: HAI prevalence was significantly lower in 2015 compared with 2011. This is partially explained by fewer SSI and UTI, suggesting national efforts to prevent SSI, reduce catheter use and improve UTI diagnosis are succeeding. By contrast, there was no change in the prevalence of the most common HAIs in 2015, PNEU and CDI, indicating a need for increased prevention efforts in hospitals. Disclosures: All authors: No reported disclosures.